Report on First Iranian International Conference on Women’s Health Held June 14-15, 2012 in Shiraz, Iran - Najmeh Maharlouei (International Journal of Fertility and Sterility, 2013)
Women’s health is increasing identified as a global health priority. Women’s health is affected by many factors, such as the economy, environment, society, culture, religion, and biology. For this reason, the Health Policy Research Center, Shiraz, Iran decided to hold The First Iranian International Conference on Women’s Health. The aim of this conference was to provide up-to-date information on different aspects of women’s health, including healthy aging, non-communicable and communicable diseases, psycho-social aspects, health promotion, reproductive health, and nutrition. Finally, the attending specialists and experts provided recommendations to be put into practice which reinforced the recommendations for additional clinical preventive services for women, mobilizing health professionals within practice, education, and research to address the national health goals, encouraging the adoption of ongoing evidence-based prevention guidelines, gender-sensitive, and culturally appropriate, persuading all stakeholders to harmonize their endeavors on women’s health, changing the viewpoint to the women as a workforce alliance as with like men, along with considering the major role of women as the basis of the family, and improving the coverage, accessibility, and quality of women-oriented health services.